A fullerene C60 supported Ru nanoparticle composite catalyst, its preparation method and application
Patent Information
- Application Number
- CN202410717101.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-04
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-06-04
AI Technical Summary
[0006]为了解决现有技术中复合催化剂制备时操作繁琐,制备时间长的问题,本发明的目的是提供一种富勒烯C60负载Ru纳米颗粒复合催化剂及制备方法和应用,该方法利用水热合成法能够得到纯净的复合材料且无Ru的其他氧化物杂质
[0021]本发明中采用的富勒烯C60,由于分子独特的刚性球状结构,可以为金属颗粒提供良好的支撑,具有较强的机械稳定性。此外,C60其自身的中空结构为金属颗粒的锚定提供了在催化过程中,不易改变自身结构,可以有效锚定金属颗粒在其表面附着。更为重要的是,C60作为催化吸附剂可以有效改善燃料的电子结构,使得肼类燃料分子内的键合作用减弱,达到提高分解速率的目的。Ru是电子的有效调节剂,具有较高的H吸附能。Ru的加入使得C60的表面电荷分布更为均匀,更有利于肼类燃料分子的吸附,从而显示出较高的催化活性。本发明制备工艺简单,成本低,具有普适性。
Smart Images

Figure CN118719051B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of carbon-based material preparation technology, and specifically relates to a fullerene C 60 Supported Ru nanoparticle composite catalysts, their preparation methods, and applications. Background Technology
[0002] Fullerene C 60 It is a novel zero-dimensional carbon material. (C) 60 The molecule possesses a highly symmetrical spherical structure and an extremely strong ability to accept electrons, which can be used to regulate the electron cloud distribution of metal atoms; C 60 It is easily reduced to negative ions and thus possesses strong reducing properties. Therefore, it can reduce metal ions into nanoparticles, regulating C 60 Surface charge prevents structural changes. In recent decades, noble metal nanomaterials, especially gold, platinum, and ruthenium, have attracted much attention due to their unique physicochemical properties and wide range of highly active catalysts. Currently, noble metal nanomaterials are widely used in various reactions, such as hydrogenation, hydrolysis, fuel cells, and catalytic reactions.
[0003] Ru has attracted widespread attention as a promising catalyst. Ru is a Pt group metal, but its price is only 4% of Pt. Multiple studies have shown that heteroatom doping can tune the electronic structure of substrate materials, thereby optimizing their catalytic performance. Carbon materials such as graphene, carbon nanotubes, and fullerenes have high specific surface areas, exposing more active sites and improving the conductivity of catalysts to effectively promote electron transport; therefore, they are excellent catalyst supports for metal particles.
[0004] Some civilian-use gunpowder still uses the formula of one part saltpeter, two parts sulfur, and three parts charcoal powder, while C 60 It is a symmetrical, soccer ball-shaped molecular structure composed of 60 carbon atoms linked by a large π system. Unlike graphite, amorphous carbon, and diamond, it is a unique carbon allotrope. Therefore, C 60 It can itself be used as an additive for liquid rocket propellants. The report believes C 60 The particles possess strong pressure resistance. Based on this characteristic, C 60 It can be used as a propellant additive, which makes the propellant grain less prone to deformation and improves properties such as specific impulse and heat of combustion. Furthermore, during the combustion of liquid propellants, C... 60 The disruption of the cage structure releases additional tension and binding energy, which can promote the complete combustion of liquid propellants. Therefore, C was designed... 60 @Ru composite catalysts are used in the thermocatalytic reaction of liquid propellants, which can significantly improve the performance parameters of fuels, such as calorific value.
[0005] However, traditional methods for reducing noble metal ions into metal particles often require the introduction of a strong reducing agent (such as NaBH4) into the system, and the amount of this agent must exceed the theoretical feed amount. This results in the generation of solid byproducts or waste acid and gas, making the operation cumbersome. Furthermore, subsequent separation and purification steps increase the preparation cost. In addition, the reduction rate of the reducing agent is limited, meaning that the metal ions require more time to react and be converted. Summary of the Invention
[0006] To address the problems of cumbersome operations and long preparation times in the preparation of composite catalysts in existing technologies, the purpose of this invention is to provide a fullerene C 60 This paper discloses a Ru-supported nanoparticle composite catalyst, its preparation method, and its application. The method utilizes a hydrothermal synthesis approach to obtain a pure composite material free of other Ru oxide impurities. The prepared composite catalyst exhibits high catalytic activity and stable active material in the catalytic reaction of liquid propellants, showing promising application prospects in the field of thermocatalysis. Furthermore, the preparation method is simple, energy-efficient, and quick.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0008] A fullerene C 60 A rapid preparation method for Ru-supported nanoparticle composite catalysts includes the following steps:
[0009] Fullerene C 60 After being added to a solvent and subjected to a hydrothermal reaction, the mixture was washed and dried to obtain C. 60 suspension;
[0010] Ruthenium salt solution with C 60 The suspension was mixed to obtain fullerene C 60 Supported Ru nanoparticle composite catalyst.
[0011] Furthermore, fullerene C 60 The ratio of the amount of the solvent to the amount of the solvent is 5-20 mg: 10-20 mL.
[0012] Furthermore, the solvent is ethanol.
[0013] Furthermore, the concentration of the ruthenium salt aqueous solution is 5-20 mg / mL.
[0014] Furthermore, ruthenium salt aqueous solution with C 60 The volume ratio of the suspension is 0.5-3.5:10-20.
[0015] Furthermore, the ruthenium salt is RuCl3.
[0016] Furthermore, the hydrothermal reaction temperature is 150-220℃, and the time is 4-12h.
[0017] Furthermore, the drying temperature is 60℃ and the drying time is 12 hours.
[0018] A fullerene C 60 Supported Ru nanoparticle composite catalyst.
[0019] A fullerene C 60 Application of Ru nanoparticle-supported composite catalysts as thermal catalysts for hydrazine-based liquid propellants.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The fullerene C used in this invention 60 Due to its unique rigid spherical molecular structure, it can provide good support for metal particles and has strong mechanical stability. Furthermore, C... 60 Its hollow structure provides a stable anchoring mechanism for metal particles, preventing structural changes during catalysis and effectively securing the particles to its surface. More importantly, C... 60 As a catalytic adsorbent, Ru can effectively improve the electronic structure of fuels, weakening the intramolecular bonds of hydrazine fuels and thus increasing the decomposition rate. Ru is an effective electron modifier with high H adsorption energy. The addition of Ru makes C... 60 The more uniform surface charge distribution is more conducive to the adsorption of hydrazine fuel molecules, thus exhibiting higher catalytic activity. The preparation process of this invention is simple, low-cost, and universally applicable.
[0022] Furthermore, this invention uses ethanol, which has weak reducing properties and is harmless to the environment, as a reducing agent, and utilizes a hydrothermal reaction to convert Ru... 3+ The process reduces Ru to metallic Ru particles. During this process, the amount of raw material and the amount of RuCl3 aqueous solution can effectively regulate the Ru particles' concentration at C. 60 The proportion of raw materials in the mixture is important; excessive use of raw materials will reduce catalytic activity, while excessive introduction of Ru particles will affect the freezing point of hydrazine fuels. Therefore, an appropriate ratio can effectively balance the effects of catalytic activity and freezing point elevation.
[0023] Furthermore, the hydrothermal reaction temperature in this invention is 150-220℃. The reaction temperature determines the reaction time for catalyst preparation. At high temperatures, the reduction of Ru particles is accelerated, which can cause Ru particle aggregation, while at low temperatures, the catalyst preparation time is prolonged. At a suitable temperature, Ru particles can have a relatively small size, thereby increasing the active specific surface area and achieving a shorter catalyst preparation time.
[0024] C prepared hydrothermally in this invention 60@Ru composite catalysts exhibit high catalytic activity and good catalytic stability for hydrazine liquid propellants, effectively improving the heat of combustion of hydrazine liquid propellants and showing potential advantages in the field of thermocatalysis. Attached Figure Description
[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art are briefly introduced below; obviously, the drawings described below are some embodiments of the present invention, and those skilled in the art can obtain other drawings based on these drawings without creative effort.
[0026] Figure 1 This invention provides a method for the rapid preparation of fullerene C10. 60 A schematic diagram of the method for supporting Ru nanoparticle composite catalysts;
[0027] Figure 2 In Example 1 of this invention, fullerene (C 60 Ru nanoparticle catalysts supported on C 60 and C 60 X-ray diffraction (XRD) pattern of @Ru;
[0028] Figure 3 In Embodiment 1 of the present invention, C 60 and C 60 @Ru's Raman spectrum;
[0029] Figure 4 In Embodiment 1 of the present invention, C 60 Scanning electron microscope (SEM) image;
[0030] Figure 5 In Embodiment 1 of the present invention, C 60 Scanning electron microscope image of @Ru;
[0031] Figure 6 In Embodiment 1 of the present invention, C 60 Transmission electron microscopy (TEM) image;
[0032] Figure 7 In Embodiment 1 of the present invention, C 60 Transmission electron microscope image of @Ru;
[0033] Figure 8 In Embodiment 1 of the present invention, C 60 and C 60 X-ray photoelectron spectroscopy (XPS) of @Ru;
[0034] Figure 9 In Embodiment 1 of the present invention, C 60and C 60 Fine X-ray photoelectron spectroscopy (XPS) spectrum of Ru 3p;
[0035] Figure 10 In Embodiment 1 of the present invention, C 60 and C 60 @Ru-catalyzed heat of combustion of amine hydrazine and unsymmetrical dimethylhydrazine (UDMH) bar chart;
[0036] Figure 11 In Embodiment 1 of the present invention, C 60 and C 60 @Ru catalytic freezing point of amine hydrazine and unsymmetrical dimethylhydrazine (UDMH) bar chart. Detailed Implementation
[0037] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention.
[0038] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention.
[0039] It should be noted that the process equipment or apparatus not specifically mentioned in the following embodiments are all conventional equipment or apparatus in the art.
[0040] Furthermore, it should be understood that the existence of other method steps before or after the combined steps, or the insertion of other method steps between these explicitly mentioned steps, does not preclude the existence of other method steps before or after the combined steps, or the insertion of other method steps between these explicitly mentioned steps, unless otherwise stated. It should also be understood that the combined connection relationship between one or more devices / apparatus mentioned in this invention does not preclude the existence of other devices / apparatus before or after the combined devices / apparatus, or the insertion of other devices / apparatus between these explicitly mentioned devices / apparatus, unless otherwise stated. Moreover, unless otherwise stated, the numbering of each method step is merely a convenient tool for identifying each method step, and not for limiting the order of the method steps or limiting the scope of the invention. Changes or adjustments to their relative relationships, without substantially altering the technical content, should also be considered within the scope of the invention.
[0041] Please see Figure 1 The present invention provides a method for rapid preparation of fullerene C 60 The method of supporting Ru nanoparticle composite catalysts, using C 60 An ethanol suspension was placed in an aqueous solution of RuCl3, and C was synthesized via hydrothermal treatment. 60@Ru composite catalysts can be used for the catalytic reaction of hydrazine liquid propellants to increase the combustion heat of hydrazine liquid propellants.
[0042] Specifically, the present invention provides a rapid method for preparing fullerene C 60 The method for supporting Ru nanoparticle composite catalysts includes the following steps:
[0043] Step 1, weigh 5-20mg C 60 Disperse the mixture in 10-20 mL of ethanol using ultrasonication to obtain C. 60 A suspension; in which ethanol is a weak reducing agent;
[0044] Step 2: Prepare 0.5-3.5 mL of an aqueous solution of 5-20 mg / mL RuCl3; wherein, the cation in the metal salt is Ru, and although the anion can be changed, other salts have poor solubility in aqueous solution, so RuCl3 is selected in this invention.
[0045] Step 3: In a forced-air drying oven, react the aqueous solution of RuCl3 with C 60 The suspension was mixed and transferred to a 25 mL reaction vessel. The mixture was reacted in a forced-air drying oven at 150-220 °C for 4-12 h. The solution was then centrifuged at 6000-10000 r / min for 30-60 min. After repeated washing with water and ethanol, the solution was dried in a forced-air drying oven at 60 °C for 12 h to obtain fullerene C. 60 Supported Ru nanoparticle composite catalyst.
[0046] In this invention, the reaction temperature is 150-220℃ because ethanol, which is weakly reducing, requires a certain high temperature to enhance its reducing power. However, ethanol itself has a low boiling point, and excessively high temperatures can lead to excessive pressure inside the reactor during the reaction, which could be dangerous. Therefore, this temperature range was chosen as the reaction temperature.
[0047] Step 4, for fullerene C 60 The Ru nanoparticle composite catalyst was characterized to determine its elemental composition and surface structure.
[0048] Step 5, compare with pure C 60 The catalytic effect of the composite catalyst prepared in this invention on hydrazine liquid propellants was determined.
[0049] Specifically, the prepared composite catalyst was used in amine hydrazine and unsymmetrical dimethylhydrazine liquid propellants, respectively, and its effects on the heat of reaction and freezing point of the two propellants were tested to demonstrate that C 60 @Ru composite catalyst for the highly efficient catalytic effect of hydrazine liquid propellants.
[0050] Example 1
[0051] Step 1: Weigh 10mg of C 60 The sample was dispersed in 15 mL of ethanol solution to obtain C. 60 Suspension.
[0052] Step 2: Prepare a 10 mg / mL RuCl3 aqueous solution and add 1.0 mL of RuCl3 solution to the suspension obtained in Step 1 to obtain a mixed solution.
[0053] Step 3: Transfer the mixed solution to a 25mL reaction vessel and place it in a forced-air drying oven at 180℃ for 6 hours.
[0054] Step four: Centrifuge the solution obtained in step four at 10000 rpm for 30 minutes. After repeated washing with water and ethanol, dry in a forced-air drying oven at 60°C for 12 hours to obtain C. 60 @Ru composite catalyst.
[0055] Step 5, take the obtained C 60 @Ru composite catalysts were used in amine hydrazine and unsymmetrical dimethyl hydrazine liquid propellants, respectively. The effects of their reaction heat and freezing point on the two propellants were tested, demonstrating their highly efficient catalytic effect on hydrazine-based liquid propellants.
[0056] Taking the preparation method disclosed in Example 1 as an example, C prepared hydrothermally 60 The @Ru composite catalyst can effectively improve the heat of combustion of hydrazine-based liquid propellants. Furthermore, the preparation process of this invention is simple, low-cost, universally applicable, and produces catalysts with high purity. It exhibits high catalytic activity and good catalytic stability for hydrazine-based liquid propellants, showing potential advantages in the field of thermocatalysis.
[0057] Please see Figure 2 , Figure 2 It can be seen from C 60 The diffraction peaks of @Ru are in perfect agreement with the standard card (JCPDS NO. 81-2220), indicating that the prepared sample is free of impurities. A (0 0 2) crystal plane with C is present at position 10.81°. 60 Interlayer spacing; additionally, distinct diffraction peaks appear at 17.7°, 20.79°, 21.7°, and 30.9°, corresponding to the (2 2 0), (3 1 1), (2 2 2), and (422) crystal planes, and are associated with C. 60 In comparison, C 60 @Ru retained C 60 The diffraction peaks were observed, but the characteristic peaks of Ru metal were not seen, indicating that Ru in C 60The surface deposition was minimal and the particles were small, with no signal of other Ru oxides detected, indicating that Ru in C 60 The surface exists in the form of a metallic phase and has no other oxide forms.
[0058] Please see Figure 3 The figure shows C before and after Ru load. 60 Raman characterization tests were performed. Notably, the Raman data showed that the spectra remained the same before and after Ru loading, indicating that the introduction of Ru did not affect C. 60 Its own structure. Furthermore, after Ru is loaded, C... 60 @Ru's Raman spectrum shows a slight broadening and redshift (≈1cm) -1 This indicates that the introduction of Ru widened C. 60 The spacing between C atoms in the sample resulted in a small amount of lattice strain and defects, which is more conducive to improving catalytic performance.
[0059] Please see Figure 4 C in the figure 60 The SEM image clearly shows C. 60 The surface is not smooth, but rather an ordered, irregular surface, which is more conducive to the growth of Ru particles on the surface. This structure provides a large number of loading sites for Ru loading. More importantly, C... 60 Its inherent cage-like structure provides high mechanical stability, enabling it to exhibit more stable catalytic performance in catalytic reactions.
[0060] Please see Figure 5 The SEM image in the figure, after Ru loading, retains C. 60 The surface structure itself is uneven, which is consistent with the results described by XRD. Furthermore, in C... 60 Numerous particles were clearly visible on the surface, providing preliminary confirmation of the successful loading of Ru particles.
[0061] Please see Figure 6 The high-resolution C in the figure 60 The TEM image clearly shows the rough surface of C60, with a distinct lattice spacing of 0.51 nm, attributed to C. 60 The (2 2 0) crystal plane.
[0062] Please see Figure 7 TEM images after the introduction of Ru show a large amount of Ru(C) 60 Black spots on the surface) particles enter C 60 The lattice structure, consistent with Raman spectroscopy findings, further confirms the successful loading of Ru. Furthermore, the composite catalyst surface retains a lattice spacing of 0.51 nm, indicating that Ru loading did not alter the C... 60 The original structure.
[0063] Please see Figure 8 C 60 With C 60 The XPS full spectrum of @Ru confirms the successful introduction of Ru, with no other elemental impurities. The C 1s chromaticity is attributed to the raw material C. 60 The unavoidable carbon pollution in the air and the O 1s are attributed to the unavoidable oxidation of the sample surface.
[0064] Please see Figure 9 The high-resolution XPS spectrum revealed a fine spectrum of Ru 3p, with the peaks at 463.2 and 485.4 eV attributed to C. 60 @Ru represents the metallic state of Ru, while the original C... 60 The failure to detect a spectral signal in Ru 3p further confirms the successful loading of Ru.
[0065] Please see Figure 10 In C 60 The effect of Ru composite catalyst on the heat of combustion of amine hydrazine and unsymmetrical dimethylhydrazine was determined. The figure shows that the introduction of Ru significantly increases the heat of combustion of both hydrazine-based liquid propellants. Specifically, in pure C... 60 Under the catalytic action of [catalyst], the heats of combustion of amine hydrazine and unsymmetrical dimethylhydrazine are 12.5433 kJ / mol. -1 and 13.8793 kJ mol -1 In C 60 Under the action of the @Ru composite catalyst, the combustion heats of amine hydrazine and unsymmetrical dimethyl hydrazine increased by 9.62% and 27.6% respectively compared with the original values, indicating that C 60 @Ru composite catalysts can significantly increase the calorific value of liquid propellants, thereby improving the combustion performance of hydrazine-based liquid propellants.
[0066] Please see Figure 11 The figure shows C 60 and C 60 The effects of @Ru on the freezing point temperatures of amine hydrazine and unsymmetrical dimethylhydrazine, respectively. As can be seen from the figure, the addition of the composite catalyst has little effect on the freezing point of the propellant, still allowing the liquid propellant to react at relatively low temperatures. Specifically, the addition of C... 60 After the @Ru composite catalyst was applied, the freezing points of amine hydrazine and unsymmetrical dimethyl hydrazine were t, respectively. 胺肼 ≥-57.0℃ and t 偏二甲肼 ≥-56.6℃.
[0067] Example 2
[0068] Step 1: Weigh 5mg of C 60 The sample was dispersed in 10 mL of ethanol solution to obtain C.60 Suspension.
[0069] Step 2: Prepare a 5 mg / mL RuCl3 aqueous solution and add 0.5 mL of RuCl3 solution to the suspension obtained in Step 1 to obtain a mixed solution.
[0070] Step 3: Transfer the mixed solution to a 25mL reaction vessel and place it in a forced-air drying oven at 150℃ for 12 hours.
[0071] Step four: Centrifuge the solution obtained in step four at 6000 rpm for 60 minutes. After repeated washing with water and ethanol, dry in a forced-air drying oven at 60°C for 12 hours to obtain C. 60 @Ru composite catalyst.
[0072] Step 5, take the obtained C 60 @Ru composite catalysts were used in amine hydrazine and unsymmetrical dimethyl hydrazine liquid propellants, respectively. The effects of their reaction heat and freezing point on the two propellants were tested, demonstrating their highly efficient catalytic effect on hydrazine-based liquid propellants.
[0073] Example 3
[0074] Step 1: Weigh 20mg of C 60 The sample was dispersed in 20 mL of ethanol solution to obtain C. 60 Suspension.
[0075] Step 2: Prepare a 20 mg / mL RuCl3 aqueous solution and add 3.5 mL of RuCl3 solution to the suspension obtained in Step 1 to obtain a mixed solution.
[0076] Step 3: Transfer the mixed solution to a 25mL reaction vessel and place it in a drying oven at 220℃ for 4 hours.
[0077] Step four: Centrifuge the solution obtained in step four at 10000 rpm for 20 minutes. After repeated washing with water and ethanol, dry in a forced-air drying oven at 60°C for 12 hours to obtain C. 60 @Ru composite catalyst.
[0078] Step 5, take the obtained C 60 @Ru composite catalysts were used in amine hydrazine and unsymmetrical dimethyl hydrazine liquid propellants, respectively. The effects of their reaction heat and freezing point on the two propellants were tested, demonstrating their highly efficient catalytic effect on hydrazine-based liquid propellants.
[0079] Example 4
[0080] Step 1: Weigh 15mg of C60 The sample was dispersed in 15 mL of ethanol solution to obtain C. 60 Suspension.
[0081] Step 2: Prepare a 15 mg / mL RuCl3 aqueous solution and add 2.5 mL of RuCl3 solution to the suspension obtained in Step 1 to obtain a mixed solution.
[0082] Step 3: Transfer the mixed solution to a 25mL reaction vessel and place it in a forced-air drying oven at 180℃ for 6 hours.
[0083] Step four: Centrifuge the solution obtained in step four at 8000 rpm for 40 minutes. After repeated washing with water and ethanol, dry in a forced-air drying oven at 60°C for 12 hours to obtain C. 60 @Ru composite catalyst.
[0084] Step 5, take the obtained C 60 @Ru composite catalysts were used in amine hydrazine and unsymmetrical dimethyl hydrazine liquid propellants, respectively. The effects of their reaction heat and freezing point on the two propellants were tested, demonstrating their highly efficient catalytic effect on hydrazine-based liquid propellants.
[0085] Example 5
[0086] Step 1: Weigh 10mg of C 60 The sample was dispersed in 20 mL of ethanol solution to obtain C. 60 Suspension.
[0087] Step 2: Prepare a 10 mg / mL RuCl3 aqueous solution and add 3.0 mL of RuCl3 solution to the suspension obtained in Step 1 to obtain a mixed solution.
[0088] Step 3: Transfer the mixed solution to a 25mL reaction vessel and place it in a forced-air drying oven at 160℃ for 8 hours.
[0089] Step four: Centrifuge the solution obtained in step four at 7000 rpm for 45 minutes. After repeated washing with water and ethanol, dry in a forced-air drying oven at 60°C for 12 hours to obtain C. 60 @Ru composite catalyst.
[0090] Step 5, take the obtained C 60 @Ru composite catalysts were used in amine hydrazine and unsymmetrical dimethyl hydrazine liquid propellants, respectively. The effects of their reaction heat and freezing point on the two propellants were tested, demonstrating their highly efficient catalytic effect on hydrazine-based liquid propellants.
[0091] The composite catalyst preparation process in this invention is simple, requires minimal equipment, and yields a pure composite catalyst. This method has considerable versatility. Successful loading of Ru does not change C. 60 The original structure, while ensuring considerable mechanical strength and multiple active sites, guarantees the successful introduction of Ru into C. 60 In the crystal lattice. When composite catalysts are used to catalyze hydrazine liquid propellants, they can significantly improve their calorific value without significantly affecting the freezing point of the propellant itself, allowing the propellant to maintain its combustion performance at relatively low temperatures. This has certain application value in the field of thermocatalysis of hydrazine propellants.
[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the specific implementation of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A fullerene C 60 The application of Ru-supported nanoparticle composite catalysts as thermal catalysts for hydrazine-based liquid propellants is characterized by... The composite catalyst is prepared by the following method: Step 1, weigh 5-20mg C 60 Disperse the mixture in 10-20 mL of ethanol using ultrasonication to obtain C. 60 suspension; Step 2: Prepare 0.5-3.5 mL of an aqueous solution of 5-20 mg / mL RuCl3; Step 3, react the aqueous solution of RuCl3 with C 60 The suspension was mixed, reacted at 150-220℃, centrifuged, washed, and dried to obtain fullerene C. 60 Supported Ru nanoparticle composite catalyst.
2. The fullerene C according to claim 1 60 The application of Ru-supported nanoparticle composite catalysts as thermal catalysts for hydrazine-based liquid propellants is characterized by... The reaction time is 4-12 h.
3. The fullerene C according to claim 1 60 The application of Ru-supported nanoparticle composite catalysts as thermal catalysts for hydrazine-based liquid propellants is characterized by... The drying temperature was 60 ℃ and the drying time was 12 h.
4. The fullerene C according to claim 1 60 The application of Ru-supported nanoparticle composite catalysts as thermal catalysts for hydrazine-based liquid propellants is characterized by... The centrifugation rate is 6000~10000 r / min, and the centrifugation time is 30~60 min.
Citation Information
Patent Citations
Composite catalyst capable of replacing iridium catalyst as well as preparation method and application of composite catalyst
CN113845398A
